A gift of fire social, legal, and ethical issues for computers and the internet - Baase, Sara (Pearson Education, 2003)
This book explores social, legal, philosophical, ethical, political, constitutional and economic implications of computing from a computer scientist's point of view. It covers the issues individuals face as members of a technological society and offers guidance for professionals in computer-related fields. One of the book's goals is to develop computer professionals who understand the implications of what they create and how it fits into society at large. Chapter topics cover privacy and personal information, encryption and interception of communications, freedom of speech in cyberspace, intellectual property, computer crime, computers and work, broader issues on the impact and control of computers, and professional ethics and responsibilities. For programmers and software engineers.